Changes in the Spectral Characteristics of Aluminum Films Deposited under Assisting Argon Ion Beam - Umnov S. P. Sergey Pavlovich; Asainov O. Kh. Oleg Khaydarovich; Popova S. N.; Lemachko A. N. (Materials Science and Technologies, 2015)
Title screen